Evaluation of Radiological Health Risks in Popularly Consumed Brands of Sachet Water in Nigeria - Aladeniyi, Kehinde; Olowookere, Christopher Jimoh; Khandaker, Mayeen Uddin; Alsufyani, Sultan J. (Frontiers in Public Health, 2022)
Radiological investigation of 35 brands of most popularly used sachet drinking water in Ondo state, Nigeria has been carried out using a spectrometric method for evaluating the concomitant health risks to the members of the public. Activity concentrations of the investigated radionuclides 40K, 226R, and 228Ra were in the range from 16.35 ± 4.10 to 199.94 ± 38.40 Bq L−1 with an arithmetic mean (AM) of 66.22 ± 54.99 Bq L−1, from 1.35± 0.79 to 17.06 ± 5.13 Bq L−1 with an AM of 6.88 ± 3.66 Bq L−1, and from 1.95 ± 0.08 to 17.22 ± 3.87 Bq L−1 with an AM of 9.49 ± 4.98 Bq L−1, respectively. The determined annual effective doses and the corresponding excess lifetime cancer risks due to 226Ra and 228Ra were found to exceed the acceptable limits of 0.1 mSv y−1 and 10−3 respectively, as suggested by the World Health Organization (WHO). This implies a non-negligible carcinogenic health hazard due to the intake of the surveyed drinking water, especially for the lactating babies (0–1) y and teenagers (12–17) y. The data from this research may form an invaluable component of radiometric values of the database in Nigeria, as well as the world for setting up guidelines and control policies for the use of sachet water.